Relapses in the process of desistence from offending - Muskała, Maciej (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
Many offenders follow the „ zigzag path”, interlacing many times criminal and noncriminal stages. The aim of this survey review is to show, on the example of the Self- Regulatory Model of Relapse Prevention analyses (SRM-r in modified version) the variety of ways and courses of action that an offender (mainly sexual) may follow in the process of desistance from offending.